Synthesis, antiviral activity, and structure-activity relationship of 1,3-benzodioxolyl pyrrole-based entry inhibitors targeting the Phenyl43 cavity in HIV-1 gp120 - Curreli, Francesca (ChemMedChem, 2018)
The pathway by which HIV-1 enters host cells is a prime target for novel drug discovery because of its critical role in the HIV-1 life cycle. The HIV-1 envelop glycoprotein gp120 plays an important role in initiating virus entry by targeting the primary cell receptor CD4. We explored the substitution of bulky molecular groups in region I in the NBD class of entry inhibitors. Previous attempts at bulky substitutions in that region abolished the antiviral activity, even though the binding site is hydrophobic. We synthesized a series of entry inhibitors containing 1,3-benzodioxolyl moiety or its bioisostere, 2,1,3-benzothiadiazole. The introduction of the bulkier groups was well tolerated, and despite only minor improvements in antiviral activity, the selectivity index (SI) improved significantly.